Chemical inhibitors as potential allied for CO2 replacement in gas hydrates reservoirs: Sodium chloride case study - Gambelli A. M.; Castellani B.; Filipponi M.; Nicolini A.; Rossi F. (World Congress on Mechanical, Chemical, and Material Engineering, Proceedings of the 6th World Congress on Mechanical, Chemical, and Material Engineering, 2020)
In previous experimental works we proved how the presence of sodium chloride may influence the replacement of methane contained into hydrate with carbon dioxide. Even if its chemical inhibitor effect is well known and documented in literature, the possibility of having different behaviours in function of the gaseous species involved in hydrate formation has not been explored. The first step of our research proved how NaCl inhibitor effect is more pronounced in methane hydrate formation rather than carbon dioxide one. That leads to a higher difference between temperature-pressure conditions describing the two species equilibrium curves and, thus, to greater possibilities of intervening in the replacement process in order to perform it and increasing both the amount of methane recovered and the quantity of carbon dioxide permanently stored. Two replacement tests were carried out in presence of 40 g/l of salt dissolved in water; then results were compared with two other tests previously realized with the same experimental apparatus but using pure demineralised water. The inhibitor effect of sodium chloride is well visible in the significantly lower quantity of methane hydrate formed in the first phase of tests. The same effect was observed during the carbon dioxide formation step, but its intensity was lower. In conclusion the use of NaCl led to a higher percentage of methane recovered and carbon dioxide stored, even if both quantities are lower than the respective value reached in tests carried out using demineralised water.